2003
DOI: 10.1103/physreve.67.056220
|View full text |Cite
|
Sign up to set email alerts
|

Noise-covered drift bifurcation of dissipative solitons in a planar gas-discharge system

Abstract: The trajectories of propagating self-organized, well-localized solitary patterns (dissipative solitons) in the form of electrical current filaments are experimentally investigated in a planar quasi-two-dimensional dc gas-discharge system with high Ohmic semiconductor barrier. Earlier phenomenological models qualitatively describing the experimental observations in terms of a particle model predict a transition from stationary filaments to filaments traveling with constant finite speed due to an appropriate cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…For gas discharge systems the friction function has been determined from experimental data and in line with the above considerations a velocity-dependent friction function was found that exhibits a velocity domain of negative friction (Bödeker et al, 2003). The SET model has been used to study the dynamics of single active Brownian agents moving in ratchet potentials Fiasconaro et al, 2008;Burada and Lindner, 2012) and performing foraging movements in two-dimensional planes (Ebeling et al, 1999Erdmann et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For gas discharge systems the friction function has been determined from experimental data and in line with the above considerations a velocity-dependent friction function was found that exhibits a velocity domain of negative friction (Bödeker et al, 2003). The SET model has been used to study the dynamics of single active Brownian agents moving in ratchet potentials Fiasconaro et al, 2008;Burada and Lindner, 2012) and performing foraging movements in two-dimensional planes (Ebeling et al, 1999Erdmann et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This type of bifurcation is well known from reaction-diffusion (see, for instance, [54,55,56,57,58] and references therein) and hydrodynamic systems (see, for instance, [59,60,61,62] and references therein), where it mediates the transition between steady and travelling structures. In our system it breaks the reflectional symmetry of the sitting droplets leading to moving asymmetric droplets and acompanying travelling asymmetric adsorbate profiles.…”
Section: The Drift-pitchfork Bifurcationmentioning
confidence: 99%
“…Illustration of the model: free diffusion within the channel and channel walls in y-and z-directions (reflective boundaries). Table 1 Applications of intrinsic transport coefficients Turbulence [3] Human tremor [7] Engineering [4] Surface sciences [8] Economics [5] Traffic [9] Time-delayed systems [6] Porous materials [2] Reaction-diffusion systems [10] that the definition of diffusion tensors by means of BD theory is not affected by the presence or absence of external or internal forces. More precisely, the evolution of the MSD components will of course depend for large times on the detailed forces acting on and between the fluid particles in a nanoporous material.…”
Section: Resultsmentioning
confidence: 99%